Problem-Based Learning and Inquiry-Based Learning Models in Learning Arithmetic Sequences and Series in High School - Hanum Ulfiatus Sufiyah; Budi Cahyono; Nadhifah Nadhifah; Bunga Ihdanorra (Jurnal Pendidikan MIPA, 2026)
This study aims to compare the effectiveness of Problem-Based Learning (PBL) and Inquiry-Based Learning (IBL) models in improving the critical thinking skills of tenth-grade high school students on the topic of Arithmetic Sequences and Series. The research employed a quantitative approach using a Matching Pretest–Posttest Comparison Group Design. The study population consisted of six classes of tenth-grade students at SMAN 16 Semarang that were normally distributed, homogeneous, and had similar average initial abilities. Due to time constraints and the need to ensure consistent implementation of learning treatments, three classes were selected through cluster random sampling. Class X-01 was assigned as Experimental Group I using the PBL model, class X-02 as Experimental Group II using the IBL model, and class X-03 as the control group using a conventional learning model. Data collection was conducted using pretest and posttest instruments designed to measure students’ critical thinking skills. The instruments were validated before the implementation. Data analysis was conducted using an independent samples t-test to determine the effectiveness of the PBL and IBL models compared to the conventional model. Furthermore, a paired samples t-test followed by an N-gain analysis was used to compare the effectiveness between the PBL and IBL models. The results indicated that both PBL and IBL models were effective in improving students’ critical thinking skills compared to the conventional learning model. However, the N-gain analysis showed that students taught with the PBL model experienced greater improvement in critical thinking skills than those taught with the IBL model. Therefore, it can be concluded that although both learning models are effective, the Problem-Based Learning model is more effective than the Inquiry-Based Learning model in enhancing critical thinking skills of grade X high school students in learning Arithmetic Sequences and Series. Keywords: inquiry-based learning (IBL), critical thinking skills, problem-based learning (PBL).